Inaugural KS Inglis address: making Australian media history. Issue 1 (February 2019) - Griffen-Foley, Bridget
This address considers the development of media history as a field of research in Australia. It takes the form of a historiographical excursion, beginning with a focus on the press, and then extending to broadcasting, and touching on the work of KS Inglis as a through line. After considering what I identify as a historiographical blossoming since the 1980s, I extend my gaze to the tools and institutions for media history that have emerged, including online resources, a conference series and a research centre. Finally, I use my own 1990s research into the Packer empire to illustrate how some of the techniques for doing media history have changed in the past 20 years. In doing so, I reflect on both the benefits, and the limitations, of digital tools and techniques for Australian media historians.